Challenges to Employing Shared Decision Making With Adults Under Community Supervision Who Have a Mental Illness - Matejkowski, Jason (Frontiers in Psychiatry, 2021)
Adults under community corrections supervision and who have a mental illness (MI) are expected to comply with conditions of release which often include involvement with supportive social services. The rates of technical violation, arrest, and incarceration that result from failure to comply with these mandates are exceedingly high. Shared decision making (SDM) among officer-supervisors and client-supervisees is a promising approach to promote engagement in community corrections services among supervisees who have MI. This paper reviews recent research on SDM and identifies three barriers to its implementation in this context: (1) a lack of role clarity, (2) a predilection for risk avoidance, and (3) stigma toward supervisees. Empirically supported recommendations are suggested to aid in overcoming these obstacles, facilitate SDM, and promote recovery among this population: (1) unification of supervisor rehabilitative and public safety roles, (2) maximizing opportunities for self-determination through low-stakes events and/or enhancement of supervisee strengths and capabilities, and (3) supervisor training in principles of mental health recovery.